PENDEKATAN JELAJAH ALAM SEKITAR (JAS) PADA MATA KULIAH SISTEMATIKA HEWAN - Fajar Adinugraha (Jurnal Pro-Life, 2018)
The research objective is to describe the Jelajah Alam Sekitar (JAS) approach in Sistematika Hewan. It also to know the students ' respond of learning with the Jelajah Alam Sekitar (JAS) approach. Beside that, the research objective is to know the students' interest to the Jelajah Alam Sekitar (JAS) approach. The research is a descriptive quantitative study which uses survey and literature study method. The learning activities with the Jelajah Alam Sekitar (JAS) approach in Sistematika hewan are 1) group discussion, 2) field study, 3) practicum, 4) instructional games, 5) lecturing method, 6) project/ task giving, 7) final exam / test, and 8) practical responses. The students' response to learning by the Jelajah Alam Sekitar (JAS) approach is 89% in good category (good and very good). Students' interest with the Jelajah Alam Sekitar (JAS) approach is 96% in interest category (interest and very interest).Keywords: Jelajah Alam Sekiar (JAS), learning approach, students’ response, students’ interest